Pathophysiology and genetics of salt-sensitive hypertension - Maaliki, Dina; Itani, Maha M.; Itani, Hana A. (Frontiers in Physiology, 2022)
Most hypertensive cases are primary and heavily associated with modifiable risk factors like salt intake. Evidence suggests that even small reductions in salt consumption reduce blood pressure in all age groups. In that regard, the ACC/AHA described a distinct set of individuals who exhibit salt sensitivity, regardless of their hypertensive status. Accumulating data has shown that salt sensitivity is an independent risk factor for cardiovascular events and mortality. However, despite extensive research, the pathogenesis of salt-sensitive hypertension is still unclear and tremendously challenged by its multifactorial etiology, complicated genetic influences, and the unavailability of a diagnostic tool. In addition, hypertensive individuals are at a greater risk for COVID-19 infections and are more likely to progress to severe disease complications and death. So far, the important roles of the renin-angiotensin-aldosterone system, sympathetic nervous system, and immune system in the pathogenesis of salt-sensitive hypertension have been appreciated. In the first part of this review, we focus on how the systems mentioned above are aberrantly regulated in salt-sensitive hypertension. We follow this with an emphasis on genetic variants in those systems that are associated with and/or increase predisposition to salt sensitivity in humans. We also provide possible explanations on the link between hypertension pathogenesis and worsened COVID-19-related outcomes.